Enhancement of Knowledge Regarding Worm Diseases in Sungai Madang Village, Sungai Tabuk District, South Kalimantan - Lisda Hayatie; Hendra Wana Nur'amin; Erida Wydiamala; Isnaini; Hilma Wardatina; Kartika Veranisa Putri; Ika Novitasari; Andi Azizah M Budiarman (PT FORMOSA CENDEKIA GLOBAL, 2023)
Sungai Madang Village, located in Sungai Tabuk District, poses a heightened risk of intestinal worm infections due to its proximity to the river. Many residents lack awareness of these infections. Thus, our community service initiative focuses on providing essential health information about worm infections, including risk factors, consequences, and prevention through deworming medications. Our methods involve discussions, lectures, and interactive Q&A sessions. Evaluation includes pre- and post-test assessments, with 39 participants, mainly housewives, involved. In conclusion, our community service significantly increased participants' worm infection knowledge by 59%. We aim to empower households, especially housewives, to better protect their families against worm infections.